A consistent assessment of social welfare by two methodologies: The theory and evidence from the Luxembourg Income Study database - Stanisław Maciej Kot; Piotr R. Paradowski (Gdansk University of Technology, Faculty of Management and Economics, 2024)
Research background: Applied welfare economics offers various social welfare functions (SWF) for appraising income distributions. Social planners commonly use two SWFs: SWFε implied by income inequality aversion (ε) and SWFv implied by rank inequality aversion (v). However, a voluntary choice of ε or v may result in inconsistent assessments of social welfare embodied in a given income distribution. Purpose of the article: We search for the combinations of ε and v that guarantee consistent assessments of social welfare, inequality and poverty embodied in a given income distribution. Methods: We propose estimating the pairs (ε,v) by solving the system of two nonlinear equations. The first equation comprises the equally distributed equivalent incomes derived from SWFε and SWFv . The second equation comprises the benchmark incomes. A small increase in income below the benchmark income reduces inequality, whereas a small increase above the benchmark income increases inequality. The system of these equations can be solved numerically. Findings and Value added: We have estimated ε, v, and related characteristics for selected Latin America and Caribbean countries using Luxembourg Income study database data.
Keywords: C10; D30; D60; I30; O15; 330; social welfare; Atkinson Index; Generalised Gini Index; inequality; poverty